Marika Daniilidou, MD. The First Female Orthopaedic Surgeon in Greece. (June 2022) - Savvidou, Olga D.; Megaloikonomos, Panayiotis D.; Vlachaki, Asimina; Melissaridou, Dimitra; Vlasis, Konstantinos; Papagelopoulos, Panayiotis J.
Dr Marika Daniilidou was born in 1902 in Asia Minor. Her family was forced to immigrate to Greece, in 1922. Despite the horrendous difficulties of the era, she pursued undergraduate and postgraduate studies in the University of Berlin, Germany, and she specialized in orthopaedic surgery. In 1937, she became the first female certified orthopaedic surgeon in Greece. In 1947, she was the only female orthopaedic surgeon among the 22 founders of the Hellenic Association of Orthopaedic Surgery and Traumatology (HAOST). She became a true role model for the next generations of Greek women surgeons.